2019
DOI: 10.1051/bioconf/20191304014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and impact of recent climate trends on grape composition in north-east Italy

Abstract: Climate is the most relevant factor influencing the ripening of high quality grapes to produce a given wine style. This notion should be taken into account, given the increase of extreme weather events (EWE) related to climate change. Under this evolving climate scenario, North-East Italian wine regions have seen a recent expansion, potentially disregarding optimal planting choices. The use of marginal land, indeed, could lead to the establishment of vineyards in areas where it is not possible to take advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Extreme weather has a major influence in vineyard regions. Events such as warm and cold temperature extremes, drought, extreme rain, hail, frost or thunderstorms have significant impacts in the productivity and quality of wine [24,25]. For the period 1986-2005, the Baixo Corgo region had less extreme maximum and minimum temperatures, resulting for example in less frost days (Tmin < 0 • C) or summer days (Tmax > 25 • C), when compared to Douro Superior [26].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Extreme weather has a major influence in vineyard regions. Events such as warm and cold temperature extremes, drought, extreme rain, hail, frost or thunderstorms have significant impacts in the productivity and quality of wine [24,25]. For the period 1986-2005, the Baixo Corgo region had less extreme maximum and minimum temperatures, resulting for example in less frost days (Tmin < 0 • C) or summer days (Tmax > 25 • C), when compared to Douro Superior [26].…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…Previous studies already demonstrated the role of some climatic variables in grape berry quality parameters [7,13,14,31,32], some of them using long-term historical data for a few variables [7]. To our knowledge, this is the only study that uses a long-time series of biochemical data in field conditions, for many berry quality aspects (berry weight, titratable acidity, pH, potential alcohol, anthocyanins and TPI): maximum of 19 years for Douro region (1999-2017) and a minimum of six years for Alentejo region (2012)(2013)(2014)(2015)(2016)(2017).…”
Section: Introductionmentioning
confidence: 99%
“…In wine production, climate is likely the most critical factor for achieving optimal grape characteristics, and produces a desired wine style (Cogato et al, 2019). Bunch zone temperature affects the phenolic profile by changing the expression level of anthocyanin synthesis-related genes, to finally determining the color and antioxidant activities of the wine (Azuma et al, 2019;de Oliveira et al, 2015;Tang et al, 2017).…”
Section: Resultsmentioning
confidence: 99%